TREM2 Regulates Heat Acclimation-Induced Microglial M2 Polarization Involving the PI3K-Akt Pathway Following EMF Exposure - He, Gen-Lin; Luo, Zhen; Shen, Ting-Ting; Wang, Ze-Ze; Li, Ping; Luo, Xue; Yang, Ju; Tan, Yu-Long; Wang, Yuan; Gao, Peng; Yang, Xue-Sen (Frontiers in Cellular Neuroscience, 2020)
Heat acclimation (HA) exerts anti-inflammatory effects and improves functional outcomes via enlarged cytoprotective reserves and physiologically conserved adaptive responses. The function of triggering receptor expressed on myeloid cells-2 (TREM2) has been described within microglia with a specific activated phenotype, which play important neuroprotective roles by controlling of local inflammation and promoting tissue repair. We previously demonstrated that electromagnetic field (EMF) exposure can induce pro-inflammatory responses and a decrease in phagocytosis in microglial cells, but information on phenotype regulation by HA is limited. Given the association between TREM2 and phenotype regulation, we investigated the TREM2-related signaling mechanism induced by HA in EMF-stimulated N9 microglial cells (N9 cells). The effects of esiRNA and pharmacological agents on HA-plus-EMF-stimulated microglia were investigated by measuring the production of cytokines and the expression of biomarkers, PI3K, and Akt using Western blotting and a fluorescence microscope. We found that EMF exposure significantly increased the production of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6), CD11b, and CD86 and, decreased the levels of anti-inflammatory cytokines (IL-4 and IL-10) and CD206 and Arg1 in the culture supernatant of N9 cells. HA treatment clearly decreased the secretion of TNF-α, IL-1β, and IL-6 and the expression of CD11b and CD86 and enhanced the production of IL-4 and IL-10 and the expression of CD206 and Arg1. TREM2 esiRNA and selective inhibitor of PI3K clearly decreased anti-inflammatory cytokine production, M2 marker expression, and phosphorylation of PI3K and Akt following HA plus EMF stimulation. These results indicate that EMF exposure can induce the M1 microglial phenotype, while HA treatment changes the microglial phenotype from M1 to M2. TREM2 and PI3K-Akt inhibition significantly increases M1 polarization and abolishes M2 polarization, leading to the elimination of the cross-tolerance protective effect of HA against EMF exposure. Therefore, this study enhances the understanding of microglial phenotype changes that underlie the neuroprotective effect of HA against EMF exposure and provides important clues for future research.